EARLY PALEOZOIC GRANITOID BATHOLITHS OF THE ALTAI-SAYAN FOLDED REGION (LATERAL-TEMPORAL ZONING AND SOURCES) - Rudnev S.N.; Vladimirov A.G.; Kruk N.N.; Ponomarchuck V.A.; Babin G.A.; Borisov S.M. (My University, 2004)
This communication discusses the issue of the formation of Early Caledonian batholiths based on comparative analysis of their age and Nd-Isotope characteristics in thee Altai-Kuznetsk -Batenev segment dominated by collisions of the arc-seamount type and the Tuva-Mongolia segment dominated by collisions related to the amalgramation of a synonymous microcontinent and the Tannuol are. We have analyzed original materials and published the results of U-Pb, Ar-Ar, Rb-Sr, and Sm-Nd isotopic studies in Tuva, the Shoriya Mountains, Kuznetsk Alatau, and Batenev Range.
Keywords: Paleozoic; Paleozoic; Палеозой